2010
DOI: 10.1590/s0100-40422010001000031
|View full text |Cite
|
Sign up to set email alerts
|

Solvation simplified

Abstract: Recebido em 24/5/10; aceito em 28/9/10; publicado na web em 16/11/10The effects of solvents on chemical phenomena is complex because there are various solute-solvent interaction mechanisms. Solvatochromism refers to the effects of solvents on the spectra of probes. The study of this phenomenon sheds light on the relative importance of the solvation mechanisms. Solvation in pure solvents is quantitatively analyzed in terms of a multi-parameter equation. In binary solvent mixtures, solvation is analyzed by consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…(ii) As discussed for probes of distinct chemical classes in binary mixtures of water with organic solvents and with ILs, this nonideal behavior is due to PS of the probe by one component of the mixture. The extent of this PS depends on the components of the binary mixture and the hydrophobicity of the probe; more hydrophobic probes show more deviation from linearity. This agrees with the larger deviation of the more hydrophobic p -RB.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…(ii) As discussed for probes of distinct chemical classes in binary mixtures of water with organic solvents and with ILs, this nonideal behavior is due to PS of the probe by one component of the mixture. The extent of this PS depends on the components of the binary mixture and the hydrophobicity of the probe; more hydrophobic probes show more deviation from linearity. This agrees with the larger deviation of the more hydrophobic p -RB.…”
Section: Resultsmentioning
confidence: 54%
“…(iii) We treated this PS according to a model discussed elsewhere, in which the medium is composed of a mixture of water (W), the organic solvent (S), and a “complex” one (S–W) formed by hydrogen bonding between the two pure solvents. This model was discussed in detail elsewhere; we give here the essentials, as summarized by eqs –: Here, the concentrations are given on the mole fraction scale, ( m ) is the number of solvent molecules that perturb the intramolecular charge transfer within the probe, hence affecting the value of E T (probe). Note that m is not the solvation number of the probe.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 It was reported that the effects of solvents on MOF synthesis and structure are complicated as a result of various solution− solvent interaction mechanisms. 21 The reaction medium in a synthesis procedure can be greatly affected by the polar properties; therefore, the selection of solvents may profoundly impact the derived product. Moreover, the polarity of solvents can be enriched by adding less polar constituents.…”
Section: Introductionmentioning
confidence: 99%